Perbandingan Financial Distress pada Perusahaan Sub Sektor Konstruksi BUMN yang Terdaftar di Bursa Efek Indonesia (BEI) Era Presiden Susilo Bambang Yudhoyono dan Presiden Joko Widodo - Siti Masrofah; Gilang Kharisma Putra (Jurnal Publikasi Manajemen Informatika, 2024)
The study aims to analyze the comparison of financial distress levels in the construction sub sector companies of BUMN listed on the Indonesian Stock Exchange (BEI) during the presidency of Susilo Bambang Yudhoyono and Joko Widodo. The quantitative method is used in this study to analyze financial data obtained from the annual reports of companies listed in the BEI. The main variables used in the study include relevant financial ratios such as the working capital ratio to total assets, the ratio of profit before interest and tax to the total asset, the profit ratio before tax to total liabilities smoothly, the sales ratios to total Assets. The data collected covered the period of two reigns, the Susilo Bambang Yudhoyono era (2009-2012) and the Jokowi era (2019-2022). The analysis was conducted using descriptive statistical techniques and paired sample t-test tests to identify significant changes in financial distress during the two leadership periods. This research found that there was a significant difference in the level of financial distress between the two eras. The findings make important contributions to understanding how economic policies and leadership changes can affect the financial health of BUMN companies in the construction sector, as well as providere commendations for future financial risk management.